Opportunities for Closing the Gap in HIV Diagnosis, Treatment, and Viral Load Suppression in Children in Malawi: Results From a 2015–2016 Population-based HIV Impact Assessment Survey. Issue 11 (November 2021) - Jonnalagadda, Sasi; Auld, Andrew; Jahn, Andreas; Saito, Suzue; Bello, George; Sleeman, Katrina; Ogollah, Francis M.; Cuervo-Rojas, Juliana; Radin, Elizabeth; Kayira, Dumbani; Kim, Evelyn; Payne, Danielle; et al.
Abstract : Background: Control of the pediatric HIV epidemic is hampered by gaps in diagnosis and linkage to effective treatment. The 2015–2016 Malawi Population-based HIV impact assessment data were analyzed to identify gaps in pediatric HIV diagnosis, treatment, and viral load suppression. Methods: In half of the surveyed households, children ages ≥18 months to <15 years were tested using the national HIV rapid test algorithm. Children ⩽18 months reactive by the initial rapid test underwent HIV total nucleic acid polymerase chain reaction confirmatory testing. Blood from HIV-positive children was tested for viral load (VL) and presence of antiretroviral drugs. HIV diagnosis and antiretroviral treatment (ART) use were defined using guardian-reporting or antiretroviral detection. Results: Of the 6166 children tested, 99 were HIV-positive for a prevalence of 1.5% (95% confidence intervals [CI]: 1.1–1.9) and 8.0% (95% CI: 5.6–10.5) among HIV-exposed children. The prevalence of 1.5% was extrapolated to a national estimate of 119, 501 (95% CI: 89, 028–149, 974) children living with HIV (CLHIV), of whom, 30.7% (95% CI: 20.3–41.1) were previously undiagnosed. Of the 69.3% diagnosed CLHIV, 86.1% (95% CI: 76.8–95.6) were on ART and 57.9% (95% CI: 41.4–74.4) of those on ART had suppressed VL (<1000 HIV RNA copies/mL). Among all CLHIV, irrespective of HIV diagnosis or ART use, 57.7% (95% CI: 45.0–70.5) had unsuppressed VL. Conclusions: Critical gaps in HIV diagnosis in children persist in Malawi. The large proportion of CLHIV with unsuppressed VL reflects gaps in diagnosis and need for more effective first- and second-line ART regimens and adherence interventions. Abstract : Supplemental Digital Content is available in the text.